Sistem Perdagangan Multilateral dalam Kerangka WTO Suatu Observasi Terhadap “Rule-based System” - Warouw, Adolf (Indonesian Journal of International Law, 2004)
The multilateral trading system as it now applies is a rule-based system comprising a comprising a complex set of rules as articulated in various WTO agreements. The system is the ultimate choice for nations if they were establish trade relations among nations in a good order and to more enhance the stability and predictability and to better suit the interests of least developed and developing countries. The implementations of those rules have been more advantageous to developed countries, while the developing countries do not have the capability tto implement those rules. The concessions that have been given away do not meet with the expected benefit out of their participation in this multilateral regime. Such situation greatly affects developing countries in the implementation and the effectiveness of WTO rules. The current round of trade negotiations needs to make correction to this legitimacy gao to ensure a fair gain from the multilateral trading system.